Development of the mechanism of the state control in the financial and budget sphere - A. V. Rusavskaya; T. P. Voronchenko (Путеводитель предпринимателя, 2020)
In the recent years development offorms and methods of the state financial control acquires special relevance in view of a lack of budgetary funds and conditions under which there is an opportunity to evade from control procedures. There is a number of shortcomings of legislative nature, budgetary planning and performance monitoring of use of budgetary funds which need to be solved. In these conditions to actually plan some ways ofdevelopment of the mechanism of control in the financial and budget sphere.